Understanding the influence of the MomConnect programme on antenatal and postnatal care service utilisation in two South African provinces: a realist evaluation protocol - Peter Delobelle; Eveline M Kabongo; Ferdinand C Mukumbang; Edward Nicol (BMJ Open)
Introduction Timely antenatal care (ANC) and postnatal care (PNC) attendance decrease maternal and child mortality by improving maternal and child health (MCH) outcomes. Mobile health or mHealth has been identified as an effective way of improving the uptake of MCH services. The MomConnect programme is an mHealth initiative launched by the National Department of Health of South Africa in August 2014 to support MCH. Although widely used, there is a limited understanding of how, why, for whom and under which health system conditions, the implementation of MomConnect improves the health-seeking behaviour of pregnant women and mothers of infants in ANC and PNC facilities. This paper describes the protocol for a realist evaluation of the MomConnect programme, to provide a theory-based understanding of how, why and under what healthcare conditions the MomConnect programme works or not.Method and analysis We will use the realist evaluation approach through its research cycle conducted in three phases. In phase I, a multimethod elicitation study design will be used, including a document review, key informant interviews and a scoping review to formulate an initial programme theory of the MomConnect intervention. Content and thematic analytic approaches will be used to analyse the data that will be fitted into a realist framework to formulate the initial programme theory. In phase II, a multi-case study design will be applied using a multimethod approach in two South African provinces. In each case, a theory-testing approach underpinned by the hypothetico-deduction analytic model will be used to test the initial programme theory. Surveys, interviews and focus group discussions will be conducted with various programme actors and analysed using appropriate methods. Phase III will entail refining the tested/modified programme theory through cross-case analysis.Expected outcomes An improved understanding of how and why the MomConnect intervention improves the health-seeking behaviour of pregnant women and mothers of infants, and the health system conditions that influence its implementation.Ethics and dissemination Ethics approval was granted by the Stellenbosch University Ethics Committee (S18/09/189). The protocol has been designed and the study will be conducted in line with the principles of the Declaration of Helsinki (1964).